The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1093/bja/aep379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnesium sulphate on intraoperative neuromuscular blocking agent requirements and postoperative analgesia in children with cerebral palsy

Abstract: I.V. magnesium sulphate reduces rocuronium requirements and postoperative analgesic consumption in children with CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 35 publications
5
53
0
Order By: Relevance
“…Studies by Na et al, [29] Benhaj et al [17] and Hwang et al [31] are consistent with our finding that there existed an inverse relation between the dose of magnesium infused and total dose of morphine required. They say that post-operative serum magnesium was higher in magnesium infused group which consumed less post-operative analgesia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Studies by Na et al, [29] Benhaj et al [17] and Hwang et al [31] are consistent with our finding that there existed an inverse relation between the dose of magnesium infused and total dose of morphine required. They say that post-operative serum magnesium was higher in magnesium infused group which consumed less post-operative analgesia.…”
Section: Discussionsupporting
confidence: 93%
“…Analysis on studies in patients undergoing general anaesthesia showed that post-operative pain scores was significantly low in magnesium infused group. [14,17,[29][30] Studies on peri-operative IV magnesium done in patients undergoing spinal anaesthesia also reported significantly lower mean pain score. [31][32][33] Post-operative pain scores were also lower when magnesium was infused epidurally.…”
Section: Discussionmentioning
confidence: 98%
“…The results of the aforementioned study were almost similar to our findings. In a study by Na on 61 patients with cerebral palsy (CP) who had undergone orthopedic surgery, pain score, the dose of rocuronium, and the use of analgesic drugs in the group who had received 50 mg/kg of magnesium sulfate bolus injection and then 15 mg/kg during surgery was lower than the placebo group (17). In another study that was done in 2008 on 48 patients by Benhaj Amor, pain score and the amount of morphine consumption in the group who had received 50 mg/kg of magnesium sulfate before surgery and 0.5 g/h after surgery was lower compared to the group who had received normal saline.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have focused on the direct enhancing effects of magnesium on the neuromuscular blockade [37-40]. In contrast, others concluded that a perioperative adjuvant magnesium sulfate administration reduced requirements for nondepolarizing neuromuscular blockers [15,29,33,41-43]. …”
Section: Muscle Relaxationmentioning
confidence: 99%